Biomarkers of patient intrinsic risk for upper and lower airway injury after exposure to the World Trade Center atrocity. Issue 9 (September 2016) - Zeig‐Owens, Rachel; Nolan, Anna; Putman, Barbara; Singh, Ankura; Prezant, David J.; Weiden, Michael D.
Abstract : Background: High rates of upper and lower airways disease have occurred in Fire Department of the City of New York (FDNY) workers exposed to the World Trade Center (WTC) disaster site. Most experienced acute declines in pulmonary function, and some continued to experience decline over 14 years of follow‐up. Similarly, some with rhinosinusitis had symptoms requiring sinus surgery. Aim: To increase generalizability of biomarker investigation, we describe biomarkers of risk for upper and lower airway injury that do not require stored serum. Methods: We review WTC biomarker literature. Results: Cytokines expressed in stored serum from the first 6 months post‐9/11 can identify individuals at higher risk for future abnormal pulmonary function. Conclusion: This research will help identify individuals at high risk of lung and sinus disease that develop after these, or future, irritant exposures for intensive monitoring and treatment. It may also identify targets for effective therapeutic interventions. Am. J. Ind. Med. 59:788–794, 2016. © 2016 Wiley Periodicals, Inc.